Excitation of isomeric low-lying level of nucleus ¹⁸¹Ta by relativistic electrons - Dikiy, N.P.; Dovbnya, A.N.; Lyashko, Yu.V.; Nikiforov, V.I.; Uvarov, V.L.; Fedorets, I.D. (Вопросы атомной науки и техники, 2013)
Influence on efficiency of exciting of the E1-level ¹⁸¹Ta with energy 6.24 keV of neutron-capture reaction and photonuclear processes by means of the processes caused by passage of powerful electron beam through tantalum is studied. Strengthening of reaction yield ¹⁸¹Ta(γ,2n)¹⁷⁹Ta and neutron-capture reaction ¹⁸¹Ta(n,γ)¹⁸²Ta by means of high intensity of high-energy electrons are discovered. Розглянуто вплив процесiв, обумовлених проходженням потужнострумового пучка електронiв через тантал, на швидкiсть заселення Е1-рiвня ¹⁸¹Ta з енергiєю 6,24 кeВ, на радiацiйне захоплення нейтронiв i фотоядернi процеси. Виявлено посилення фотоядерної реакцiї ¹⁸¹Ta(γ,2n)¹⁷⁹Ta i реакцiї радiацiйного захоплення нейтронiв ¹⁸¹Ta(n,γ)¹⁸²Ta при високiй iнтенсивностi високоенергетичних електронiв. Рассмотрено влияние процессов, обусловленных прохождением сильноточного пучка электронов через тантал, на скорость заселения E1-уровня ¹⁸¹Ta с энергией 6,24 кэВ, на радиационный захват нейтронов и фотоядерные процессы. Обнаружено усиление фотоядерной реакции ¹⁸¹Ta(γ,2n)179Ta и реакции радиационного захвата нейтронов ¹⁸¹Ta(n,γ)¹⁸²Ta при высокой интенсивности высоко энергетических электронов.